(untitled) (Patan Pragya, 2024)
Plant extracts are a conceivably better substitute for corrosion prevention of metallic materials that are acceptable to the environment. This study investigates about the application of the organic fraction of Mahonia nepalensis (MN) bark extract for the corrosion protection of mild steel (MS) in 1 M H2SO4. The separation of the organic layer from MN bark extracts were subjected to column chromatography using the dichloromethane (DCM)-methanol as solvent for the separation of alkaloids. The identification and quantification of compounds of the DCM-methanol fraction was performed by liquid column mass spectrometry (LC-MS). Fourier transform infrared (FTIR) and ultraviolet-visible spectroscopy (UV-Vis) were used to characterize the DCM-methanol fraction of the MN extract. Potentiodynamic polarization (PDP) and electrochemical impedance spectroscopy (EIS) were used to investigate the corrosion inhibition of MS using the DCM-Methanol fractions in 1M H2SO4. The DCM-Methanol fraction containing 1.2 ppm berberine exhibited an inhibitory efficiency (IE) of 84.35%, suggesting that it is a viable and reasonable choice for preventing MS corrosion. The potentiodynamic polarization reflected a decrease in the hydrogen reduction, as indicated by the suppression of the cathodic current without altering the reaction process. According to open circuit potential and polarization curves, it showed mixed inhibitory behavior. EIS analysis also found a decrease in double-layer capacitance and an increase in charge transfer resistance. EIS and energy dispersive X-ray spectroscopy (EDX) in a scanning electron microscope (SEM) confirmed inhibitor molecules have adhered to the MS surface to form a protective coating